Plant health and quality of eucalyptus urophylla x eucalyptus grandis seedlings receiving phosphite and silicon application - Silva, Thiago Tássio de Sousa [UNESP]; Spada, Grasiela [UNESP]; de Faria, Marianne Fidalgo [UNESP]; Goulart, Lívia Mara Lima; Furtado, Edson Luiz [UNESP]; Passos, José Raimundo Souza [UNESP]; Guerrini, Iraê Amaral [UNESP] (FapUNIFESP (SciELO), 2019)
The forest sector is one of the major contributors in social, economic and environmental terms to Brazil. Considering this sector, eucalyptus planting is the most important of the segment, representing 5.56 million hectares. The first step in the eucalyptus forest establishment process is seedling production, which in Brazil is done through cloning, ensuring the quality of the seedlings planted in the nursery. However, one of the main challenges in nurseries is pathogen control and the variety of eucalyptus species and hybrids that are susceptible to disease. The use of phosphite and silicon is hypothesized to decrease bacteriosis severity level and maintain seedling quality in forest nurseries. Therefore, to test these hypotheses, this study aimed to verify the effect of phosphite and silicon application on bacteriosis control and Eucalyptus urograndis seedling quality in a commercial nursery. Experimental design was completely randomized with four replicates and ten treatments (“Zincazot”, “Fitofós-Cu”, “Fitofós-K”, “Fitofós-Zn-Mn”, “Silamol”, “Amorux”, “Fitofós-Cu + Terra-sorb”, “Fitofós-K + Terra sorb”, “Fitofós-Zn-Mn + Terra Sorb”, and control); each replicate consisted of a tray containing 176 seedlings including control, which did not receive any application. The applications were performed on the leaves, from seven days before ministumps were collected from the mini-clonal garden until seedlings completed 120 days old. Results were compared according to Tukey’s test at 5% probability. Application of products containing phosphite and silicon did not reduce the severity of bacteriosis caused by Xanthonomas sp. in Eucalyptus urograndis seedlings in the nursery. There was no significant effect of treatments on the evaluated quality patterns. At 120 days, seedlings of all treatments, except control, had adequate survival rate, evidencing a positive effect of treatments on this variable, which is of great economic importance for a commercial nursery.
Fitossanidade e qualidade de mudas de eucalyptus urophylla x eucalyptus grandis em função da aplicação de fosfito e silício
Keywords: Bacteriosis; Eucalyptus; Phosphite; Seedling quality; Severity